2021
DOI: 10.3390/molecules26082283
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Climate Change and Herbivory to Affect the Release and Atmospheric Reactions of BVOCs from Boreal and Subarctic Forests

Abstract: Compared to most other forest ecosystems, circumpolar boreal and subarctic forests have few tree species, and are prone to mass outbreaks of herbivorous insects. A short growing season with long days allows rapid plant growth, which will be stimulated by predicted warming of polar areas. Emissions of biogenic volatile organic compounds (BVOC) from soil and vegetation could be substantial on sunny and warm days and biotic stress may accelerate emission rates. In the atmosphere, BVOCs are involved in various gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 171 publications
0
10
0
Order By: Relevance
“…In addition to facilitating trophic and multi-trophic interactions, HIPVs are involved in information transfer between plants, which is often referred to as plant–plant communication [ 10 ]. Stem feeding on conifers induces substantial VOC emissions [ 11 ], which provide potentially strong HIPV cues to other organisms in the community [ 12 ]. However, despite such HIPV-mediated between-plant communication being documented in numerous plant species [ 10 ], earlier studies have chiefly focused on herbaceous and broadleaved woody plants, with conifers largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to facilitating trophic and multi-trophic interactions, HIPVs are involved in information transfer between plants, which is often referred to as plant–plant communication [ 10 ]. Stem feeding on conifers induces substantial VOC emissions [ 11 ], which provide potentially strong HIPV cues to other organisms in the community [ 12 ]. However, despite such HIPV-mediated between-plant communication being documented in numerous plant species [ 10 ], earlier studies have chiefly focused on herbaceous and broadleaved woody plants, with conifers largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The release of the BVOCs is regulated by plant hormones, notably jasmonates, salicylic acid, and ethylene [50][51][52]. The sensitivity of BVOC emissions to biotic and abiotic stresses has been extensively reviewed [31,53,54]. Blends of HIPVs can be specific to a plant species and the herbivores feeding on it [51].…”
Section: Bvocs As a "Wireless" Plant Communication Mediummentioning
confidence: 99%
“…Temperature is an important factor controlling BVOC emissions (Fitzky et al, 2019;Yáñez-Serrano et al, 2020). Temperature changes directly affect the biochemical reactions in the metabolic pathways which produce BVOCs or have indirect effects like lengthening of the growing season (Peñuelas and Staudt, 2010;Yu et al, 2021). As temperatures increase, the enzymatic activities of synthesis are enhanced, BVOCs vapor pressure is increased and the resistance of the diffusion pathway is lowered.…”
Section: Emission Of Biogenic Volatile Organic Compoundsmentioning
confidence: 99%
“…Liu et al reported that since 2013 an increase in temperature and biogenic emissions led to a rise in the Maximum Daily Average 8-hourly (MDA8) O 3 mixing ratio by 1-2 ppbv (Liu and Wang, 2020). However, extreme temperatures and severe heat stress can cause cellular lesions and a drop in photosynthesis that may not improve upon return to cooler temperatures and reduce BVOCs emission (Yu et al, 2021).…”
Section: Emission Of Biogenic Volatile Organic Compoundsmentioning
confidence: 99%